2013
DOI: 10.1530/rep-13-0127
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal/permeability-increasing protein in the reproductive system of male mice may be involved in the sperm–oocyte fusion

Abstract: Bactericidal/permeability-increasing protein (BPI) is a 455-residue (w55 kDa) protein found mainly in the primary (azurophilic) granules of human neutrophils. BPI is an endogenous antibiotic protein that belongs to the family of mammalian lipopolysaccharide (LPS)-binding and lipid transport proteins. Its major function is to kill Gram-negative bacteria, thereby protecting the host from infection. In addition, BPI can inhibit angiogenesis, suppress LPS-mediated platelet activation, increase DNA synthesis, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…To confirm that GSK3 did indeed reside within dense bodies, epididymal sections were dual‐labeled with combinations of anti‐GSK3, anti‐HSPD1, and anti‐BPI antibodies, the latter being established markers of the dense body population (27, 36). All proteins strongly colocalized within the majority of dense bodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that GSK3 did indeed reside within dense bodies, epididymal sections were dual‐labeled with combinations of anti‐GSK3, anti‐HSPD1, and anti‐BPI antibodies, the latter being established markers of the dense body population (27, 36). All proteins strongly colocalized within the majority of dense bodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, although the function for BPI in FF is still unknown, the presence of BPIFA2 during the ovulatory seasons may be important to protect the female genital tract (e.g., oviduct). Also, few reports have found that BPI is expressed in the testis and epididymis of mice and appears to take part in the process of gamete interactions [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…In the male mice, BPI is speci cally expressed in the testis and epididymis (Lennartsson et al 2005). After secretion from the epididymal epithelia, BPI is transferred to membrane surface of the spermatozoa (Zhou et al 2014), and is essential for the sperm-oocyte fusion (Li et al 2013, Yano et al 2010. MPO serves as peroxidase lysosomal enzyme that produces hypochlorous acid and other highly reactive oxidants (Klebanoff et al 2012).…”
Section: Discussionmentioning
confidence: 99%